The effects of strength and conditioning interventions on serve speed in tennis players: a systematic review and meta-analysis - Deng, N.; Soh, K. G.; Xu, F.; Yang, X. (Frontiers in Physiology, 2025)
Background: Tennis performance is highly influenced by serve speed. This review aimed to evaluate and quantitatively compare the efficacy of popular strength and conditioning (S&C) training methods in enhancing the speed of the ball in the serves of tennis players.